The Anatomy of the Lamina Terminalis and Cisterna Chiasmatica at the University Teaching Hospital, Lusaka, Zambia: A Cadaveric Study - Vivienne Nambule Syamuleya; Isaac Sing’ombe; Fridah Mutalife; Sikhanyiso Mutemwa; Elliot Kafumukache; Krikor Erzingatsian (Advancement and New Understanding in Medical Science Vol. 7, 2024)
This chapter explore the anatomy of the Lamina Terminalis, the Cisterna Chiasmatica and its neurovascular relationships as seen in a Zambian population and compare with the findings in the literature. The Lamina Terminalis represents an important neuroanatomical structure by which third Ventriculostomy could be performed into the subarachnoid space through the Cisterna Chiasmatica. The Cisterna Chiasmatica is a dilatation of the subarachnoid space which lies adjacent to the Optic Chiasma and filled with freely circulating cerebral spinal fluid. Recent studies have indicated a role for Lamina Terminalis fenestration in approaching pathologies of the third ventricle. However, there is limited knowledge on the anatomical features, variations and the vasculature of the Lamina Terminalis in a Zambian population. The study was a descriptive cross-sectional design in which 32 post-mortem human cadaveric brains were systematically sampled. The Lamina Terminalis region was examined in 27 male cadavers and five female cadavers of age range between 25 and 66 years (mean 34.1 ± 9.2years). The Cisterna Chiasmatica a dilated subarachnoid space was examined in particular with neurovascular structures adjacent to the Lamina Terminalis. Data was collected using a data collection form, entered and analyzed by descriptive statistics using Statistical Package for Social Sciences (SPSS) software version 22. The base of the brain was detached from the floor of the cranial cavity and the Lamina Terminalis exposed fully by retracting both optic nerves and the optic Chiasma posteroinferiorly. The triangular Lamina Terminalis measurements were performed as the distance between the midportion of the upper aspect of the chiasma and the lower aspect of the anterior commissure (height), which averaged 8.6 ±1.0 mm. The distance between the medial edges of the optic tracts (base) averaged ±1.1 mm and the area averaged 56.9 ± 11.6 mm2. The Lamina Terminalis membrane showed variations in appearance; 20 were transparent with a large dark midline gap and 10 were less translucent with a slender midline gap and two were indistinct. The Cisterna Chiasmatica was observed as a dilated subarachnoid space adjacent to the Optic Chiasma. For neurovascular relationships, 24 cadavers showed arterioles arising from the posterosuperior aspect of the anterior cerebral artery to perforate the anterior perforating substance(s), supplying the chiasma, and optic tracts; whereas, eight cadavers showed arterioles arising posteroinferiorly and ramifying on the Lamina Terminalis. The Lamina Terminalis membrane is variably developed. There are variations in the membrane appearance, measurements and neurovascular relationships. This study suggests that routine examinations of the lamina terminalis is of great importance in neurosurgeries of pathologies of the third ventricle. These findings will supplement a knowledge gap in neuroanatomy and help prevent complications during Lamina Terminalis fenestration in approaching pathologies of the third ventricle.